Label‐free in vivo imaging of peripheral nerve by multispectral photoacoustic tomography. Issue 1 (22nd April 2015) - Li, Rui; Phillips, Evan; Wang, Pu; Goergen, Craig J.; Cheng, Ji‐Xin
Abstract : Unintentional surgical damage to nerves is mainly due to poor visualization of nerve tissue relative to adjacent structures. Multispectral photoacoustic tomography can provide chemical information with specificity and ultrasonic spatial resolution with centimeter imaging depth, making it a potential tool for noninvasive neural imaging. To implement this label‐free imaging approach, a multispectral photoacoustic tomography platform was built. Imaging depth and spatial resolution were characterized. In vivo imaging of the femoral nerve that is 2 mm deep in a nude mouse was performed. Through multivariate curve resolution analysis, the femoral nerve was discriminated from the femoral artery and chemical maps of their spatial distributions were generated.The femoral nerve was discriminated from the femoral artery by multivariate curve resolution analysis. Abstract : Iatrogenic damage to peripheral nerves is a leading cause of morbidity attributed to surgical procedures. Unintentional surgical damage to nerves is mainly due to poor visualization of nerve tissue relative to adjacent structures. Multispectral photoacoustic tomography can provide chemical information with specificity and ultrasonic spatial resolution with centimeter imaging depth, making it a potential tool for noninvasive neural imaging.